Changes in caries prevalence in 7-12-year-old children from Araraquara, São Paulo, Brazil: 1989-1995 - Ercilia Leal Dini; Ana Lígia Rozato Foschini; Ioneide Maria Gomes Brandão; Sílvio Rocha Corrêa da Silva
The aim of this study was to compare the prevalence of caries in 7-12-year-old children from Araraquara, São Paulo, Brazil, in 1989 and 1995. Systematic random samples were drawn from the population of children enrolled in public schools. The surveys were carried out by trained examiners using the DMFT index and WHO diagnostic criteria. There was an increase in the percentage of children free of caries in the permanent dentition in all age groups (from 29 percent in 1989 to 51 percent in 1995). Amongst 12 year olds, the DMFT index was 3.8 in 1989 and 2.6 in 1995. Decreases were observed in the percentages of children classified in the 1-3 DMFT index category (from 40 percent in 1989 to 31 percent in 1995) and in the 4-6 DMFT index category (26.6 percent in 1989 to 16.5 percent in 1995). There was also a reduction in the percentage of children with a DMFT of 7 or more (4.4 percent in 1989 to 1.5 in 1995). The WHO/ FDI goal for the year 2000 of a mean DMFT index no more than 3 at the age of 12 years was achieved in this population, and on-going efforts should be made to reduce the percentage of children with caries in order to achieve the WHO/FDI goals for the year 2010.